Pemetaan Ekonomi Kreatif Subsektor Kuliner di Kota Pontianak - hendarmin, Hendarmin; Kartika, Metasari (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2018)
This study aims to map the creative economy culinary subsector of Pontianak City in 2017 based on Creative Economy Indonesian Standard Industrial Classification (ISIC) and structure-conduct-performance (SCP) approach. This study also maps the characteristic of creative economy actor culinary subsector based on age and education, as well as observes the creativity of culinary subsector in Pontianak City. This study used qualitative descriptive method with study object in Pontianak City. The sampling method used was stratified random sample with 287 total samples. The result was the creative economy scopes in Pontianak City mostly are restaurants, stalls, and cafÃ©. The economy creative actor for culinary subsector in Pontianak is 40 years old in average and 51.2% had high school as their educational background. The creativity of culinary subsector in Pontianak City were 41.1% involving the trained chef, 8,4% routinely creates new menu, 14.3% consists the local cuisine, 51,2% gives culinary experience for the consumers, and 29.3% has used technology. Based on the SCP approach (1) 95.5% culinary business model in Pontianak City are independent, (2) 79.8% (229 respondents) of the creative economy actors stated they determine the price by themselves; from 229 respondents, 120 respondents determined their own prices after finding out their rival"™s prices, (3) 87.1% marketing strategy still use word of mouths marketing technique, (4) the business turnover per month ranging from IDR 400.000- IDR 80.000.000 and manpower recruiting with micro business criteria (1-4 people) for 88.2% while small business (5-19 people) for 11,8%.